Does digital transformation promote green innovation? A micro-level perspective on the Solow Paradox - Sun, Yi; He, Moyan (Frontiers in Environmental Science, 2023)
Digitalization and sustainability, as emerging trends, have long attracted both academic and industrial focuses, yet the topic has not been sufficiently investigated at the micro-firm level. Selecting Chinese listed companies from 2010 to 2021 as the research sample and adopting the two-way fixed effects model, the impact of firms’ digital transformation on their green innovation as well as the channels and mechanisms involved are investigated. The empirical results show that, firstly, the digital transformation of firms can significantly promote the quality and quantity of their green innovation. Secondly, internal control is a mediating path for digital transformation to promote green innovation, while financing constraints suppress the above effects, and top management team’s environmental attention positively moderates the promotion of green innovation by corporate digital transformation. Thirdly, the promotion effects are more pronounced in firms that are state-owned, large-scale, ecologically cost-free, and relatively highly financing constrained. The findings suggest that digital transformation has advantages in revealing the “Solow paradox” that persists in the digital era, and the synergistic development of digitalization and greening at the firm level is realistic and feasible.